Penggunaan Alat Peraga Untuk Meningkatkan Pemahaman Sains Siswa Kelas V Sd Negeri 1 Lolobata Kabupaten Halmahera Timur Tahun 2023 - Latukau, Munir (Peneliti.net, 2023)
The aim of this research is to determine student learning achievement using the demonstration method in science subjects, to increase students' understanding of the concept of the human skeleton in science subjects by using teaching aids. The subjects of this research were all class V students of SD Negeri 1 Lolobata, East Hamahera Regency with a total of 40 students. The results of this research show that the average score of students on science subjects regarding the concept of the human skeleton was low before treatment. These results show that the average score of students when given the pre-test was 3.65 and the results of the post-test is 6.72, so the comparison between pre-test and post-test is 3.07 or 84.10%. So it can be concluded that the application of learning using teaching aids to class V students at SD Negeri 1 Lolobata, East Hamahera Regency can improve student learning outcomes.